THE ROLE OF HR DEVELOPMENT IN INCREASING THE COMPETENCY OF THE STATE CIVIL APPARATUS AT THE UPTD-BSMBP OFFICE OF THE PLANTING SERVICE OF SOUTH SULAWESI PROVINCE - Khaerunnisa, Fahruni; Rakkang, Yayu; Nurhikmah, Andi Reski (Journal of Entrepreneur, Business and Management, 2024)
The Role of HR Development Against Competence Improvement of State Civil Apparatus at the Office of the UPTD-BSMBP of the Plantation Office of South Sulawesi Province, Thesis of the Management Study Program of the Faculty of Economics and Business, University of Muhammadiyah Makassar. Supervised by Supervisor I Moh. Aris Pasigai and. Nasrullah's Second Counselor This study aims to determine the Role of HR Development Against Competence Improvement of State Civil Apparatus at the UPTD-BSMBP Office of the Plantation Office of South Sulawesi Province. The type of research used is quantitative. Data collection was carried out by distributing questionnaires to 30 ASN respondents from the UPTD-BSMBP Plantation Office of South Sulawesi Province. This study uses a simple linear regression analysis method. The results of this study indicate that, based on the t test statistic, the value of t arithmetic is 6.530 t table 1.699 and a significant value 0.05. So it was concluded that HR development had a significant effect on ASN competencies HR Development and ASN CompetenceKeywords: HR Development and ASN Competence